Green Building : A New Wave In India - Mamta, Ms. (International Journal of Scientific Research and Management (IJSRM), 2015)
India is experiencing an incredible growth in the construction and real estate industry. Due to this rise in theconstruction sector raised many issues related to the environment and sustainability. As per economic policy forum, inits report mentioned that in India the energy consumption in buildings is for heating, ventilation and air Conditioneraccounts for between 45% and 65% of total electricity consumption. Another study states that the construction sectorof India emits about 22% of the total annual emission of CO2 which is very harmful for the environment. So to handlethe adverse situation a new and important concept is emerging in India that is Green Building. So this article gives youthe understanding about the green buildings, How the green building get rating from the rating agencies, Importanceof green buildings, and examples of some companies and organization that are taking the advantage of green waveand is flourishing.